WE5.7 A Comparison of Small and Large Bites Closure of Fascia in Midline Laparotomy Wounds: Experience in a District General Hospital. (9th August 2022) - Heard, Rachel; Darbi, Elmahdi; Soh, Coreen; Barker, Jonathan
Abstract: Aims: Small bites (SBC) laparotomy closure (5mm fascial bites, 5mm apart) is thought to decrease incisional hernia rates compared to large bites (LBC) closure (1cm bites, 1cm apart). A colorectal surgeon in our centre changed practice following the STITCH trial. We aimed to assess whether this change affected outcomes. Methods: All midline laparotomy patients immediately before and after the change in practice in 2017 were considered for inclusion. Data on demographics, co-morbidities, operation details, length of stay (LoS), complications and outcome were gathered from operation notes and electronic patient records. Follow up was censored at 12 months to make groups comparable. Results: 80 patients were included (38 SBC; 42 LBC), undergoing laparotomy from August 2014-December 2020. Age, gender and ASA grade were comparable between groups. 58% SBC; 71% LBC were emergency cases. LoS was 7 days (range 3–166) for SBC; 11 (5–369) LBC. Overall wound complication rates were similar (23.7% SBC; 19% LBC, p=0.61). There were 4 (10.5%) burst abdomens following SBC and 2 (4.8%) following LBC (p=0.21). 1 (2.6%) SBC and 3 (7.1%) LBC developed incisional hernia at 12 months. Conclusions: SBC did not result in decreased wound complications: although incisional hernia rate and LoS were reduced, there was a (non-significant) higher rate of burst abdomens in SBC. The latter may reflect a learning curve effect of a new technique. This study suggests SBC is feasible in a DGH, but long-term outcomes of SBC are yet to become apparent, which may have affected results in this cohort.